Caribbean masala : Indian identity in Guyana and Trinidad - Ramsaran, Dave; Lewis, Linden, 1953- (Caribbean studies series (Jackson, Miss.), 2018)
"Certain historical and social forces brought disparate groups of people to the Caribbean, in some cases, under extreme oppression. In 1833, the abolition of slavery in the British Empire led to the import of exploited South Asian indentured workers in the Caribbean. Through subsequent generations, Linden Lewis and Dave Ramsaran concentrate on the Indian descendants' processes of mixing, assimilating, and adapting in the Caribbean, while trying desperately to hold on to that which marks a group of people as distinct. In some ways, the lived experience of the South Asian community in Guyana and Trinidad represents a cultural contradiction of belonging and not belonging. In other parts of the Caribbean, South Asian people seem so absorbed by the more dominant African culture and through marriage that the issue of Indo-Caribbean heritage is often not as fraught. Much needs to be written on the Indo-Caribbean. In this collaboration based on focus groups, in-depth interviews, and observation, sociologists Lewis and Ramsaran lay out cultural context within which to develop a broader view of Indians in Guyana and Trinidad, now a majority in both countries. They address issues of race and ethnicity, but move beyond these familiar aspects to track such factors as ritual, gender, family, daily life, and the challenges of modernity. Lewis and Ramsaran gauge not only an unrelenting process of assimilative creolization on these descendants of India, but also the resilience of this culture in the face of modernization and globalization."--Provided by publisher.